Institutional Investors and Mutual Fund Governance: Evidence from Retail-Institutional Fund Twins - Evans, Richard B.; Fahlenbrach, Rüdiger (Review of Financial Studies, 2012)
[Advisors often manage multiple versions of a fund. These "twins" have the same manager and similar performance but are sold to different investors with differing abilities to select and monitor managers. Comparing investor flows in retail and institutional twins, we find that institutional investors are more sensitive to high fees and poor risk-adjusted performance. Consistent with the reduction of agency problems from greater monitoring, retail funds with an institutional twin outperform other retail funds by 1.5% per year. After the institutional twin is created, expenses decrease while measures of managerial effort at the retail fund increase.]